(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Background The concept of Essential medicines was pioneered by the WHO in 1977 to provide safe and effective treatment against the global burden of disease. Latest, 19thEML by WHO and 4th list of NLEM are published in 2015 Aims and Objectives To study the factors affecting the change in profile of Essential medicine list. Materials and Methods The EML was accessed from the official website of WHO and the NLEM from Central Drugs Standard Control Organization website, downloaded and compared. A detailed analysis of 1st and latest EML was done in terms of System wise allocation, addition and deletion of medicines Results There is steady increase in number of Essential Medicines from 204 to 414 in latest EML of WHO when compared to first list. Maximum allocation of medicines in WHO first list is for Infectious disease (53/204,26%) followed by Cardiovascular diseases (25/204,12%),Central nervous system disorders (15/204,7%) whereas in latest version of EML by WHO maximum allocation of medicines is to Infectious diseases (135/414,33%) followed by antineoplastic medicines (47/414,11%), cardiovascular disorders (32/414,8%). Maximum increase in medicines is seen with following sub categories of diseases like Antineoplastic (47), Anti viral drugs (27), Anti tubercular drugs (17), Contraceptives (16), antidotes (15). Some of the medicines like Atorvastatin, Telmisartan, Glimepiride, Thiopentone, cetirizine etc are included in NLEM 2015 but not included in WHO-EML 2015 Conclusion The study gives insight about the change in profile of medicines in essential medicine list over a period of time with respect to change in burden of disease, newer diseases , newer invention of safe and effective medicines